The Human and Social Factors of Technological Innovations: Risks And Resources Analysis Model - V. Patrakov, Eduard; de Brito Dias, Rafael; F. Frogeri, Rodrigo; I. Baturina, Lioudmila (NOvation — Critical Studies of Innovation, 2025)
This theoretical article is devoted to the human and social factors of innovations. This is due to the fact that innovation is an increasing and inevitable trend of our time, with deep impacts on society, on nature and on individuals. At the same time, innovations are related to the area of large economic risks and have quite pronounced contradictions, including in the psychological context. The article reveals the basics of studying the psychological context of innovation and the main risks associated with such a context, drawing attention to the need of developing conceptual approaches to better understand this phenomenon, as well as proper policy frameworks that address innovation under these emerging views. As a result, the author’s model for the analysis of risks and innovation resources is presented. The model includes three levels of analysis: the macro level (socio-cultural and institutional factors), the meso level (company level), and the micro level (a person as a subject, creator and/or consumer of innovations). This approach allows us not to make too sharp distinctions between the social, psychological and economic factors of innovation.